Studies in Cooperative Farming (Reports of 22 Cooperative Farming Societies) - Planning Commission (Planning Commission, 1956)
In the beginning the farm had only an area of 101:93 -acres in 80 plots. The present number of plots is 167 covering an area of 209.60 acres. All this land is in a permanently settled area and the 10 members of the farm own permanent tenancy rights, in it. 70 acres of this farm are irrigated, for paddy cultivation only from a seasonal river. The river is blocked and the water inundates this acreage. Recently a tubewell has also been sunk in the village under the Sugarcane Development Scheme. 20 acres of the farm are deriving benefit from this source of irrigation. The land is ¦comprised in 20 different blocks of various sizes.
Programme Evaluation Organisation
Programme Evaluation Organisation Planning Commission